2019
DOI: 10.1101/622886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Increasing Importance of Fellowships and Career Development Awards in the Careers of Early-Stage Biomedical Academic Researchers

Abstract: Excessive competition for biomedical faculty positions has ratcheted up the need to accumulate some mix of high-quality publications and prestigious grants to move from a training position to university faculty. How universities value each of these attributes when considering faculty candidates is critical for understanding what is needed to succeed as academic faculty. In this study I analyzed publicly available NIH grant information to determine the grants first-time R01 (FTR01) awardees held during their tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
12
2
Order By: Relevance
“…A recent study of publicly available data indicates that the proportion of faculty receiving their first large research program grant (an R01 through the NIH) with a history of funding as a trainee (F and K awards through the NIH) is significantly increasing, driven mostly by K awards. Pickett states: "While not a prerequisite, a clear shift is underway that favors biomedical faculty candidates with at least one prior training award" ( Pickett, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of publicly available data indicates that the proportion of faculty receiving their first large research program grant (an R01 through the NIH) with a history of funding as a trainee (F and K awards through the NIH) is significantly increasing, driven mostly by K awards. Pickett states: "While not a prerequisite, a clear shift is underway that favors biomedical faculty candidates with at least one prior training award" ( Pickett, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nikaj and Lund examined the trajectory of researchers who had been awarded K awards during the doubling period of NIH funding (years 1998–2003) and beyond (years 2004–2016) and found that K awardees were 24.1% more likely to obtain an R01, R01 equivalent, or Research Project Grant than researchers without these awards ( 5 ). Similarly, Pickett’s analysis showed that the percentage of investigators obtaining a first-time R01 who previously were awarded F or K awards has steadily increased since 2000 ( 6 ).…”
Section: Why Support Training and Career Development?mentioning
confidence: 96%
“…The return on investment of career development support has been well documented. Several analyses examined the impact of National Research Service Award postdoctoral fellowships on subsequent NIH R01 outcomes for applicants who obtained fellowships between 1996 and 2008 ( 4 – 6 ). For example, Heggeness et al found that NIH F32 postdoctoral fellowships increased the likelihood of receiving subsequent NIH-funded research awards in general and specifically of receiving subsequent R01 awards ( 4 ).…”
Section: Why Support Training and Career Development?mentioning
confidence: 99%
“…Preprints, or manuscripts submitted to an open-access server prior to peer-reviewed publication, are becoming increasingly popular among early career researchers, particularly in the life sciences (33,34,35) and are shown to boost article citations and mentions (29)(30)(31)37). We opted to address whether this increase in preprint submissions had an impact on the academic job market.…”
Section: Demographics Of Our Applicant Survey Respondentsmentioning
confidence: 99%
“…Receiving funding as a trainee is often seen as part of a favorable research track record (32) and a recent study indicates faculty are more likely to receive a large research program grant (e.g. an R01 through NIH) if they have a history of funding as a trainee (33). We differentiated the types of funding a trainee can receive into independent funding (in which the trainee is listed as the PI and funds can often transition with the trainee to a hiring institute (e.g.…”
Section: Independent Funding and Fellowshipsmentioning
confidence: 99%